Predicting Motor Skills From Strengths and Difficulties Questionnaire Scores, Language Ability, and Other Features of New Zealand Children Entering Primary School. Issue 1 (July 2014) - Sargisson, Rebecca J.; Powell, Cheniel; Stanley, Peter; de Candole, Rosalind
<x content-type="archive" xml:space="preserve">Abstract</x> The motor and language skills, emotional and behavioural problems of 245 children were measured at school entry. Fine motor scores were significantly predicted by hyperactivity, phonetic awareness, prosocial behaviour, and the presence of medical problems. Gross motor scores were significantly predicted by the presence of medical problems. The fine motor scores of Māori children were poorer than those of Pākekā or children of other ethnicities, and right-handed children had better fine motor scores than left-handed children. There was some evidence that left-handed boys performed particularly poorly on tasks requiring fine motor skills. Children with medical problems had poorer gross motor scores than children without medical problems. Implications for the identification of problems at school entry are discussed.